1994
DOI: 10.3109/00016349409015769
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal endometritis after abdominal twin delivery

Abstract: The infectious complications of 122 consecutive abdominal twin deliveries over the period 1984-1989 were analyzed in a prospective clinical study, comparing them with 761 singleton abdominal deliveries over the period 1984-1986. The incidence of endometritis was nearly three-fold after twin deliveries and the incidence of abdominal wound infections nearly two-fold compared with singleton abdominal pregnancies (13.1/4.7% and 5.6/3.0%). The risk of amnionitis was increased ten-fold, 6 hours after rupture of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
1
0
5
Order By: Relevance
“…Previous studies have revealed an increased risk of maternal postpartum complications, such as hemorrhage and endometritis, in twin pregnancies compared to singleton pregnancies (13,14). In our study, women undergoing emergency cesarean deliveries were more likely to present infectious complications of any type (clinical, surgical wound and endometritis).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have revealed an increased risk of maternal postpartum complications, such as hemorrhage and endometritis, in twin pregnancies compared to singleton pregnancies (13,14). In our study, women undergoing emergency cesarean deliveries were more likely to present infectious complications of any type (clinical, surgical wound and endometritis).…”
Section: Discussionmentioning
confidence: 98%
“…De igual modo se está evaluando los resultados del manejo conservador para casos de rotura prematura de membranas en pretérminos, con la intención de mejorar la tasa de sobrevida perinatal. Algunos optan terminar con la gestación, debido a que existe riesgo de corioamnionitis hasta 10 veces mayor en comparación a la gestación única, con sólo 6 horas de rotura 2,36 . Otros, tomando en cuenta la viabilidad fetal, adoptan una conducta conservadora con rigurosa vigilancia feto materna y refieren resultados alentadores.…”
Section: Discussionunclassified
“…Vía de parto. La cesárea tiene frecuencia alta por indicaciones propias del gemelar, pero no hay evidencias que apoyen un uso rutinario (41); tiene morbilidad significativamente mayor que en únicos (42,43) y su prevención se inicia con la selección adecuada de los casos para el parto vaginal. La elección de la vía de parto es la última etapa del cuidado obstétrico y se ha racionalizado con el diagnóstico de corionicidad, precedente al criterio de presentación fetal lo que permite excluir de la opción vaginal a los casos inapropiados.…”
Section: Discussionunclassified